2019
DOI: 10.1016/j.cjph.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Static traversable wormholes in f(R,T)=R+2αlnT gravity

Abstract: Traversable wormholes, studied by Morris and Thorne [3] in general relativity, are investigated in this research paper in f (R, T ) gravity by introducing a new form of nonlinear f (R, T ) function. By using this novel function, the Einstein's field equations in f (R, T ) gravity are derived. To obtain the exact wormhole solutions, the relations p t = ωρ and p r = sinh(r)p t , where ρ is the energy density, p r is the radial pressure and p t is the tangential pressure, are used. Other than these relations, two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…For shape function , throat is at [20], The choice of shape function is very important as it gives the following results [33]:…”
Section: Solutions Of Throne-morris Wormhole Assuming the Redshift Function Is Constantmentioning
confidence: 99%
“…For shape function , throat is at [20], The choice of shape function is very important as it gives the following results [33]:…”
Section: Solutions Of Throne-morris Wormhole Assuming the Redshift Function Is Constantmentioning
confidence: 99%
“…Wormhole solutions have been formulated in f (R) gravity with models such as f (R) = 1/R and f (R) = R 2 [16]. Recently, traversable wormhole solutions have been studied extensively in different f (R) gravity theories with different choices of metric parameters [17,18,19,20,21,22,23,24,25]. In this study, we focus on a recently proposed model [26] with the following form of f (R):…”
Section: Introductionmentioning
confidence: 99%
“…WH solutions are admitted with anisotropic and isotropic fluids under certain conditions. Godani and Samanta [36] considered another functional form of f (R, T ) -gravity relevant for dark energy model in cosmology to obtain wormhole solutions and found that wormhole solutions are permitted without the requirement of non-exotic matter for a given type of shape function. In this paper we consider a modified f (R, T ) = f (R) + λT , where λ is a constant and f (R) = R + αR 2 to obtain wormhole solutions.…”
Section: Introductionmentioning
confidence: 99%